Surgical Hemostasis for Severe Multisystem Pelvic Injuries - I. V. Kazhanov; A. Y. Demko; V. A. Manukovsky; S. I. Mikityuk; V. A. Reva; E. A. Kolchanov; D. V. Pavlov (Неотложная медицинская помощь)
For the treatment of patients with severe multysistem pelvic trauma accompanied by pelvic bleeding, many algorithms have been proposed that have different procedures for the use of various methods of surgical hemostasis, but none of them may guarantee the complete arrest of pelvic bleeding. The purpose of this study was to estimate clinical efficacy and developed algorithm, aimed at timely diagnosis of intrapelvic bleeding and its complete arrest with the help of different methods of surgical hemostasis in patients with severe concomitant injury of the pelvis. The article analyzes the results of treatment of 168 patients with unstable pelvic ring injuries and signs of intrapelvic bleeding, who were treated in two trauma centers of the first level in St. Petersburg: I.I. Dzhanelidze St. Petersburg Research Institute of Emergency Medicine and Military Surgery Clinic of S.M. Kirov Military Medical Academy in 2010-2018. The victims were divided into two statistically homogeneous groups. In the comparison group (75 people), the pelvic ring was mechanically stabilized with the Ganz C-clamp or the anterior part of the pelvis was fixed with an external fixation device (EFD), and the arrest of the ongoing pelvic bleeding was expected due to occur due to the effect of biological tamponade. In the main group (93 people), after mechanical stabilization of the pelvic ring, various methods of surgical hemostasis were used: balloon occlusion of the aorta, pelvic tamponade, angiography with embolization. The choice of method for surgical haemostasis after trauma depended on the severity of the affected condition of hemodynamic parameters, availability of life-threatening consequences of damage to other areas of the body and the efficacy of previously applied method for intrapelvic bleeding arrest. The introduction of modern diagnostic and treatment algorithm, aimed at complete hemostasis in patients with ongoing intrapelvic bleeding reduced the overall mortality rate by 1.7 times, mortality within 24 hours of admission by 2.3 times, as well as the duration and the volume of blood transfusion therapy by 3 and 1.8 times.Authors declare lack of the conflicts of interests.